AN ANALYSIS OF PROJECT-BASED LEARNING APPROACHES IN ENHANCING ENGLISH PROFICIENCY AMONG SECONDARY SCHOOL STUDENTS - Prastawa, Singgih; Nurzaima, Nurzaima; Karimah, Saidatul; Kurniawan, Mirdan; Mafruhah, Anisatul; Haddar, Gamar Al (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research analyzes the Project-Based Learning (PBL) approach in enhancing English proficiency among secondary school students. Through an in-depth literature review, the study explores the impact of PBL on motivation, speaking and writing skills, collaboration skills, and language integration with other learning content. The findings indicate that PBL effectively improves student motivation, hones speaking and writing skills, and fosters collaboration and communication skills. The integration of English with other learning content through PBL provides a deeper and more contextual understanding. Despite implementation challenges, the long-term benefits of PBL in equipping students with relevant English language skills are highly significant.